System performance optimization of ORC-based geo-plant with R245fa under different geothermal water inlet temperatures. (March 2017) - Liu, Xinghua; Zhang, Yufeng; Shen, Jiang
Highlights: A novel comprehensive parameter was used as objective function. Pinch point temperature difference (PPTD) is significant for ORC. Optimal PPTD is related with heat source inlet temperature (HSIT). A quadratic function exists between optimal PPTD and HSIT. Abstract: Organic Rankine cycle (ORC) is effective for heat-work conversion. However, the system performance should be improved due to the high irreversible loss. The pinch point temperature difference (PPTD) is a very important parameter for the ORC-based plant and is often fixed to be a constant value, especially for low- and medium-grade heat sources. In this paper, the influence of the PPTD on the system performance was analyzed base on the laws of thermodynamics. The net power output, the product of the total thermal conductance, the size parameter (SP), and the volumetric flow ratio (VFR), were calculated. The results show that the net power output and the total thermal conductance are opposite with the PPTD. The optimal PPTD is closely correlated with the heat source inlet temperature (HSIT), and there is a quadratic function between them, with the optimal PPTD from 2 to 21 °C for the HSIT ranging from 80 to 180 °C, which can be popularized in engineering applications.